Nas teias da construção identitária socioprofissional: práticas profissionais de trabalhadores sociais pós-graduados inseridos em organizações da economia social - Diogo, Vera (Sociologia: Revista da Faculdade de Letras da Universidade do Porto, 2018)
This article is based on a research on socio-professional identification of postgraduate social workers, employed in the social economy. Under the interpretative paradigm and a qualitative methodology, two dimensions were focused: educational and socio-professional. Here, we develop on the latter, based on semi structured interviews. This study revealed three profiles – four rocky planets and a dwarf-planet; two gas giants and three iced planets – among which the centrality of education is a common trait and for two of which the organizational context is significantly relevant.